Superhero v bystander effect: Effects of fictional and non-fictional media priming on situational altruism - Aboulez, Nermine Mourad (AUC Knowledge Fountain, 2016)
Media priming is one of the most deeply-rooted and wide span theories in media studies. Previous research deploying this theory usually compared the effects of pro-social and anti-social media priming, while this study opted to compare the effects of pro-social fictional and non-fictional media content. Furthermore, the researcher attempts to examine the effects of media priming on situational altruism, as well as, measure the difference between exposure to fictional and non-fictional videos of heroic acts, when it comes to priming an actual helping behavior. An experiment was conducted using a staged manipulation of a sexual harassment situation, as a high cost help situation. The results were statistically insignificant possibly due to the relatively small sample, the one time exposure, or cultural aspects. Nonetheless, the study’s frequencies show that those exposed to non-fictional videos have a higher likelihood of acting altruistically when they encounter a run-in with a naturalistic sexual harassment situation on college campus, than those exposed to fictional videos. Additionally, fiction has been found more likely to prime pleasure-based motivations and non-fiction primes pressure-based motivations. As for the bystander barriers, the findings show that those exposed to non-fiction experience them more than those exposed to fiction.